Євген Кагаров і українська фольклористика 1920-х років - Шевчук, Т.; Новійчук, В. (Народна творчість та етнографія, 2007)
The 1920s were very good times for the Ukrainian folkloristics despite the luck of funds and complicated political situation. Such prominent folklorists as V.Perets, F.Kolessa, K. Hrushevska, D. Zelenin and Ye. V. Kaharov were actively working in the field of folklore studies. The contemporary folklorists don’t know much about Yevhen Kaharov, who was teaching in Kharkiv University during 1925–1930. This article gives very detailed descriptions of Kaharov’s scholarly achievements and scientific life, as well as description of his articles and research and social activities. It also includes the list of the materials kept in various archives in Ukraine, including the archive of the Rylsky Institute.